Radio Frequency Ablation of Liver Tumor-Influence of Vein Wall and Location of Large Vessels - Islam, MD Mohaiminul; Asadul Islam, Muhammad (British Journal of Healthcare and Medical Research, 2017)
Radiofrequency ablation (RFA) is a process that uses RF energy which is one form of electromagnetic energy to destroy cancer cells. This is a minimally invasive technique to treat some kinds of cancer and can be applied to nonsurgical patients. The frequency range of RF current is between 300 kHz to 1 MHz. Tumors from lung, liver, kidney and bone may be removed by performing RFA. Here in our model a patient specific simulator for Radiofrequency ablation (RFA) of liver tumors has been developed and the effects of the presence of blood vessel inside the liver tissue on the temperature distribution and the volume of ablation has been shown. And the effect of temperature distribution on the distance between large blood vessel and electrode tip has been shown, all these effects has been shown for two different models one is with vein wall and one without vein wall. Heat is generated within liver tumors utilizing RF energy from RF current where the RF current is generated using a power generator. With the heat generation, the tissue temperature reaches a temperature where cell death occurs. This cell death occurs when the cells are heated to approximately 50 °C or above. Temperature should not exceed 100 °C because it will cause overheating. We develop the model using ANSYS 16.2 and numerically solve the problem to view the variation of temperature around the electrode tip within the liver tissue. We consider a model with blood flow inside a vessel and which is in the vicinity of the heated tissue and a model without a vessel.